Desempenho de frangos de corte de 1 a 21 dias de idade alimentados com rações contendo extrato de leveduras e prebiótico e criados em diferentes temperaturas - Silva, Vanessa Karla [UNESP]; da Silva, Janaina Della Torre [UNESP]; Gravena, Rodrigo Antonio [UNESP]; Marques, Rafael Henrique [UNESP]; Hada, Fabricio Hirota [UNESP]; de Moraes, Vera Maria Barbosa [UNESP] (FapUNIFESP (SciELO), 2009)
The performance of broilers reared at different temperatures and fed diet with or without yeast extract and/or prebiotic in the starter phase was evaluated. One thousand, four hundred and forty 1-d male Cobb-500® were reared at different climatic chambers. The diets with or without yeast extract or prebiotic were fed only in the starter phase (1 to 7 days), and from the 8th day on all broiler were fed the same commercial diet. It was used a complete randomized experimental design, as a 3 × 2 × 2 factorial arrangement, with 3 rearing temperatures (high 34 ± 1°C, control 32 ± 2°C and low 27 ± 2°C), 2 yeast extract level (with or without) and 2 prebiotic level (with or without). High and low temperatures decreased the performance of brids at 7 and 21 days old. The inclusion of prebiotic in the pre-starter phase increased weight gain of birds under low temperature at 21 days old and the viability until 21 days old. The inclusion of yeast extract increase feed conversion at 21 days old. © 2009 Sociedade Brasileira de Zootecnia.
Performance of broilers from 1 to 21 days old fed diets with yeast extract and prebiotic, reared at different temperatures
Keywords: Heat stress; Mannanoligosaccharides; Saccharomyces cerevisiae; Started diet